Progress of in situ conservation and use of crop wild relatives for food security in a changing climate: a case of the underutilised Vigna Savi - Manda, Leonard; Idohou, Rodrigue; Agoyi, Eric Etchikinto; Agbahoungba, Symphorien; Salako, Kolawolé Valère; Agbangla, Clement; Adomou, Aristide Cossi; Assogbadjo, Achille Ephrem (Frontiers in Sustainability, 2025)
Crop wild relatives (CWRs) - wild plant taxa genetically closely related to domesticated plants - are considered an alternative pathway to solving global food insecurity in a changing climate. However, their potential contribution is undermined by fundamental knowledge gaps in taxa diversity, distributions, taxonomic affiliations, conservation strategies, and valuable traits. To address these gaps, we reviewed the literature on the progress made between 2000 and 2021 in support of in situ conservation and use of CWRs under the changing climate in five thematic areas focusing on the genus Vigna: (1) species diversity, global distribution, conservation status, gene pools, and importance of the genus; (2) CWR-in situ conservation-protected area debate; (3) cultivation and domestication of CWR populations; (4) adaptive response to drought stress; and (5) adaptive response to Striga stress. We report that 104 Vigna CWR species in five subgenera, Ceratotropis, Haydonia, Lasiosporon, Plectotropis, and Vigna, are distributed mostly in Africa and Asia. Nine species are domesticated while six are threatened. Vigna gene pools remain poorly understood. Many Vigna CWRs provide various ecosystem services for human and environmental health. Attention is increasing towards in situ conservation of CWRs, within and outside protected areas, and complemented by ex situ conservation approaches. Several Vigna CWR taxa exhibit good agronomic traits for potential cultivation and neo-domestication. Many taxa have demonstrated tolerance to drought stress and race-specific Striga resistance. We conclude that if effectively conserved and used, Vigna CWRs can contribute to sustainable and climate-resilient food systems, either as wild edible plants, new plants for neo-domestication or novel sources of genetic material for use in pre-breeding programmes to improve the resilience, quantity and quality of Vigna domesticates under the changing climate. This study could stimulate further research and policy change for effective CWR conservation and use for sustainable food security in a changing climate.